Black Colleges Across the Diaspora : Global Perspectives on Race and Stratification in Postsecondary Education. - Brown II, M. Christopher (Advances in Education in Diverse Communities: Research, Policy and Praxis., 2017)
This book examines colleges and universities across the diaspora with majority African, African-American, and other Black designated student enrolments. It engages the diversity of Black colleges and universities and explains their critical role in promoting academic excellence in higher education.